Incidence and Epidemiological Profile of Snakebites and Scorpion Stings in Northern Khuzestan Province, Southwestern Iran: A Descriptive, Analytical Study - Kassiri, Hamid (Asian Journal of Pharmaceutics (AJP), 2018)
Aim: The aim of this study was an epidemiological study of scorpion sting and snakebite in Dezful, Shush, and Gotvand Counties, located in the southwestern part of Iran. Materials and Methods: This research was a descriptive and analytical study. The information was gathered and recorded in questionnaires. Data were collected from 1756 to 89 scorpion sting and snakebite cases, respectively, during 2013. Data were analyzed by the descriptive statistical method and the Chi-square test using SPSS version 18. P < 0.05 is considered as significant difference in this study. Results and Discussion: The age distribution of cases showed that the largest rate of scorpion stings and snakebites occurred among the 15–24 (22.4%) and 25–34 (44.9%) years old groups, respectively. The most frequent of scorpion stung people was female (51.3%). However, a total of 92.1% of snakebites were male. The most frequent scorpion stings (18.2%) and snakebites (21.3%) were happened in June. The highest incidence of scorpion sting (59%) and snakebite (51.7%) cases in above-mentioned counties during 2013 was taken place in villages. Legs were more at risk of sting by scorpions (39.7%) and snakes (59.6%). Most of the scorpion sting (41.5%) and snakebite (42.7%) cases occurred in spring. A statistical significant correlation was observed between scorpion sting and age, month, season, and sting site on the body (P < 0.05). Statistical analysis showed a non-significant difference between history of sting, gender, and residence place. Scorpion stings and snakebites are the important health challenges in the tropical and subtropical areas. They are significant medical emergencies, particularly in children. Scorpionism and snakebite are considerable health hazards in Iran, especially in the rural area of south and Southwest of Iran. Conclusion: The results of this study indicated that most of the cases happened in June, spring, rural areas, and legs.